Upaya Meningkatkan Kemampuan Siswa Dalam Reading Comprehension Teks Narrative Melalui Model SQ3R di Kelas VII-E SMPN 1 Cikembar Kabupaten Sukabumi - Sri Jatmika, Susanto (Jurnal Syntax Fusion, 2022)
Joint learning activities can help spur active learning. Teaching and learning activities in the classroom can indeed stimulate active learning, but the ability to teach through small group collaboration activities will allow to promote active learning activities in a special way. What students discuss with their friends and what students teach their friends enable them to gain understanding and mastery of the subject matter. The aims of this research are: (a) Want to know the improvement of English learning achievement after the implementation of cooperative learning. (b) Want to know the effect of learning motivation B. English after the implementation of cooperative learning. (c) provide an overview of appropriate learning methods in an effort to improve student achievement and make students active in teaching and learning activities. This research uses action research three rounds ofeach round consists of four stages, namely: design, activities and observations, reflection, and revision. The targets of this study were students of class VII-E of SMPN 1 Cikembar, Sukabumi Regency, in the 2022/2023 academic year. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student achievement increased from Pre-cycle to Cycle II, namely Pre-cycle (68.42%), Cycle I (81.58%), Cycle II (94.74%). The conclusion of this study is that cooperative learning methods can have a positive effect on student achievement and motivation in class VII-E SMPN 1 Cikembar, Sukabumi Regency and this learning model can be used as an alternative learning English